The Cooperation of Grimm Brothers, Jernej Kopitar and Vuk Karadžić Sodelovanje bratov Grimm, Jerneja Kopitarja in Vuka Karadžića - Kropej, Monika (Studia mythologica Slavica, 2013)
<span style="line-height: 115%; font-family: ’Calibri’,’sans-serif’; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ’Times New Roman’; mso-bidi-theme-font: minor-bidi; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">This article is focused on Kopitar’s work for oral tradition in the eras of the Enlightenment and Romanticism, and on his contribution to South Slavic publications of folk narrative and linguistics, especially from the perspective of his cooperation with Jacob Grimm and Vuk Stefanović Karadžić. Jernej Kopitar (1780–1844), Slovene linguist, censor, and scribe in Vienna, was one of the founders of Slavic studies and the author of the renowned first Slovene scientific grammar book, entitled Grammatik der slavischen Sprache in Krain, Kärnten und Steiermark (Grammar of Slavic languages in Carniola, Carinthia and Styria 1809). He was also translator of the Freising Manuscripts (Brižinski spomeniki). As an accomplished philologist, Kopitar maintained contacts and corresponded with numerous intellectuals of that period, notably with Josef Dobrovský and the great German philologists Jacob and Wilhelm Grimm. Some of their letters have been preserved to this day. As a mentor to Vuk Karadžić, whom he encouraged to publish literary folklore, dictionaries, and grammar, he introduced Karadžić to Jacob Grimm and made references of Karadžić in his letters to Grimm, who took Karadžić under his guidance.